Physicochemical analysis of bay leaf (Syzyium polyanthum (Wight) Walp.) and its effect on healthy adults’ blood glucose - Mohd Nazri A.R.; Siti Nurain A.; Rovina K.; Nor Hayati, M; Mury, K.; Abdul Aziz, J.; Nurul Huda (Rynnye Lyan Resources, 2025)
Bay leaf (Syzygium polyanthum (Wight) Walp.), a common culinary ingredient, is known for its potential to regulate blood sugar levels. This study aimed to develop bay leaf tea, evaluate its physicochemical composition and proximate values, assess its acceptance in the community, and examine its impact on blood glucose levels. The bay leaf tea was prepared using the freeze-drying technique, which lasted for 96 hrs at -85°C. Small pieces of ground bay leaves (2 g) were placed in tea bags and stored in airtight containers. The phenolic content of the tea was analyzed using the Folin-Ciocalteu method, and its color was assessed with a colorimeter as part of the physicochemical analysis. Moisture and ash content were also measured in the tea powder for proximate analysis. A total of 33 participants took part in the bay leaf tea acceptance test to evaluate the community perception of the tea's development process. The participants were adults aged between 20 and 30 years, in good health, and not pregnant. Blood glucose levels were measured via capillary blood sampling before consumption of the tea. Participants were then instructed to refrain from consuming any food or liquids for 30 mins before a second blood glucose measurement was taken. Although 46 subjects were initially recruited, only 33 met the study’s protocol and eligibility criteria. To assess the tea’s effect, participants consumed 200 mL of bay leaf tea at 80°C. The results indicated a significant reduction in blood glucose levels after consuming the tea compared to the baseline measurements.